Minecraft. Wither without you - Gudsnuk, Kristen (Milwaukie, OR : Dark Horse Books, 2020)
Cahira and Orion are twin monster hunters who go on a mission to get their mentor back, and meet Atria, a girl cursed as a monster lure, whom they convince to join their rescue mission to use her monster-attracting abilities to find the enchanted wither.
2.8
3-6
Keywords: Twins -- Comic books, strips, etc -- Juvenile fiction; Monsters -- Comic books, strips, etc -- Juvenile fiction; Minecraft (Game) -- Comic books, strips, etc -- Juvenile fiction; Twins -- Fiction; Monsters -- Fiction; Minecraft (Game) -- Fiction; Cartoons and comics; Monster comics; Graphic novels; Comics (Graphic works)